Dearomatisation of o-xylene by P450BM3 (CYP102A1). - Whitehouse, C; Rees, N; Bell, S; Wong, L (2011)
The oxidation of o-xylene by P450(BM3) from Bacillus megaterium yields, in addition to the products formed by microsomal P450s, two metabolites containing an NIH-shifted methyl group, one of which lacks the aromatic character of the substrate. The failure of the epoxide precursor of these two products to rearrange to the more stable 2,7-dimethyloxepin suggests that ring opening is P450-mediated. With m-xylene, the principal metabolite is 2,4-dimethylphenol. The partition between aromatic and benzylic hydroxylation is primarily governed by the steric prescriptions of the active site rather than by C-H bond reactivity. It is also substrate-dependent, o- and m-xylene appearing to bind to the enzyme in different orientations. The product distributions given by variants containing the F87A mutation, which creates additional space in the active site, resemble those reported for microsomal systems.